Record frosh class projected for fall 2013 - Uribes, Tom::::::::: (2013)
At his first press conference Thursday (Aug. 1) as Fresno State's 8th president, Dr. Joseph Castro announced that a record class of 3,339 first time freshmen are expected to enroll for the fall 2013 semester